Energy distribution with DC microgrids in commercial buildings with power electronics - Wunder, Bernd; Kaiser, Julian; Fersterra, Fabian; Ott, Leopold; Han, Yunchao; März, Martin (Proceedings - 2015 International Symposium on Smart Electric Distribution Systems and Technologies, EDST 2015, 2015)
This paper describes the application of a distributed DC microgrid in a commercial environment as well as the current state of the art and standardization efforts. The introduced grid features various sources and loads being interconnected with a 380 VDC bus. Here, focus lies on the implementation of a DC fast charge station for electro mobility into a DC grid as well as to elaborate the advantages compared to charging from the AC grid. Additionally, the application of DC nanogrids in workplace environments and their combination with a superordinate DC microgrid is presented. The benefits offered by nanogrids compared to conventional AC power supply in an office are discussed as well. Finally, the hardware to realize a DC microgrid within one electrical cabinet is introduced. Its versatility to fulfill a wide range of functions in the grid is shown as well.
CRIS-Team Scopus Importer:2023-03-07
Keywords: DC charging; DC microgrid; droop control; energy distribution; nanogrid